Cancer: second cause of death among the elderly in Medellín, 2002-2006 - Luz M. Bustamante A; Sara J. Marín O; Doris Cardona A (Universidad de Antioquia, 2012)
Objective: to describe the behavior of lung, stomach, andprostate cancer mortality among the elderly in the city of Medellinfrom 2002 to 2006. Methodology: a descriptive study with asecondary information source. The study was conducted basedon the analysis of 2809 records of deaths from lung, stomach,and prostate cancer in people over 65 years. The analysis wasunivariate and bivariate. Additionally, it was accompanied bystatistical tests and had a reliability of 95 %. The average andspecific mortality rates were calculated per ten thousand elderlyindividuals. Results: the risk of dying from lung cancer was at itshighest value in 2003, with a rate of 20.27; for stomach cancer, the greatest risk was observed in 2002, with 11.88; finally, 2006was the year with the highest risk for prostate cancer, with 9.35per ten thousand inhabitants. For the three types of cancer, theaverage mortality rate over time was 37.1. Thus, cancer is thesecond leading cause of death after acute myocardial infarction.Discussion: lung, stomach, and prostate cancer pose a risk to theelderly. Moreover, the risk increases as the individuals age. Thisstudy contributes to the state of the art of the research on causesof death among the elderly.